PENDEKATAN STEWART DALAM pH DARAH YANG MENDASARI ASIDOSIS METABOLIK - Efrida Efrida; Ida Parwati; Ike Sri Redjeki (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Metabolic acidosis is the most frequent acid-base disorder in patients of the Intensive Care Unit. By conventional approach based onpH value, [HCO3–], and base deficit (BD) from blood gas analyzer (BGA) measurement are often inappropriate with the clinical stateand inadequate in explaining the mechanism of the metabolic acidosis. The Stewart approach states that the blood pH is determinedby a strong ion difference (SID), the carbon dioxide tension (pCO2), the total concentration of non-volatile weak acid. The Stewartapproach may give a better understanding of the mechanisms that underlie the metabolic acidosis. The purpose of this study is to knowthe correlation of blood pH value measurement from BGA and calculation based on Stewart approach and identifying the mechanismsthat underlie a metabolic acidosis. In this study an analytic observational cross-sectional method was used. The examined subjectsconsisted of 71 patients who were admitted with a metabolic acidosis at the ICU from July up to August 2007. All patients were measuredfor their blood pH, pCO2, [HCO3–], BD, sodium, potassium, calcium, magnesium, chloride, lactate, albumin, and phosphate. The resultwas reported as the mean and standard deviation. The data were analyzed by Pearson’s correlation test and linier multiple regression.Statistical significance was determined at p < 0.05. The mean values of blood pH measurement from BGA and blood pH calculationbased on the Stewart approach were 7.33 (0.11) and 7.49 (0.11) (r = 0.681; p < 0.001). Most patients had two underlying mechanisms ofmetabolic acidosis. Hyperlactatemia was present in 61.8%, hyperchloremia was present in 58.2% of patients. Based on this study so far,by using the Stewart approach there is an excellent and significant correlation between the blood pH measurement from BGA and bloodpH calculation. Hyperlactatemia and hyperchloremia are the main causes of the metabolic acidosis in patients of the ICU ward.